Unravelling the Metacognitive Thinking Skills of Engineering Students: Exploring the Role of Age and Gender - Kumar, Manoj; Shivanjali; Duggal, Taranjeet; Agrawal, Charul (Journal of Engineering Education Transformations, 2025)
This study aimed to investigate the metacognitive thinking skills among engineering students and explore the influence of age and gender on these skills. The Metacognitive Thinking Skills Scale developed by (Tuncer & Kaysi, 2013) was used to assess four dimensions: thinking skills, reflective skills towards problem-solving, decision-making, and alternative skills of evaluation. A sample of 270 engineering students from private colleges in Delhi NCR was taken for study. The research data was analyzed using IBM SPSS 26 and Smart PLS 4. The questionnaire demonstrated good reliability, with a Cronbach's alpha of 0.891. The data were analyzed using descriptive statistics, reliability analysis, confirmatory factor analysis, discriminant validity analysis, and structural equation modelling. The results showed that age had a significant positive impact on alternative skills of evaluation, decision-making skills, thinking skills, and reflective skills towards problem-solving among engineering students. However, gender had a minimal effect on these cognitive constructs with a slight impact on decision-making skills. The findings suggest that age plays a crucial role in the development of metacognitive thinking skills among engineering students, while gender differences are relatively insignificant in this context. Implications include educational interventions for fostering metacognitive thinking skills among engineering students.